Risk factors and management of incidental durotomy in lumbar interbody fusion surgery - Enders, Frederik; Ackemann, Amelie; Kiening, Karl; Orakcioglu, Berk (Clinical spine surgery, 2018)
Study Design: This is a retrospective study analysis. Objective:In this retrospective study we evaluated risk factors for incidental durotomy and its impact on the postoperative course. Summary of Background Data: Lumbar interbody fusion (LIF) is increasingly applied for the treatment of degenerative instability. A known complication is incidental durotomy. Materials and Methods: A cohort of 541 patients who underwent primary LIF surgery between 2005 and 2015 was analyzed. Previous lumbar surgery, age, surgeon’s experience, intraoperative use of a microscope, and the number of operated levels were assessed and the risk for incidental durotomy was estimated using the Log-likelihood test and Wald test, respectively. The association of incidental durotomy and outcome parameters was analyzed using the quantile regression model. Results: In 77 (14.2%) patients intraoperative cerebrospinal fluid (CSF) fistula was observed. Previous lumbar surgery (P<0.001), number of operated levels (P=0.03), and surgeon’s experience (P=0.01) were significantly associated with incidental durotomy. Incidental durotomy was significantly associated with a prolonged bed rest (P<0.001), hospital stay (P=0.041), and an increased use of postoperative antibiotics (P<0.001). Eleven of 77 patients with incidental durotomy (14.3%) developed postoperative CSF fistula of whom 10 (91%) needed revision surgery for dural repair. Conclusions: We could identify important risk factors for incidental durotomy in LIF surgery. In patients who had undergone previous lumbar surgery and those with multilevel disease particular precaution is required. Furthermore, we were able to verify the morbidity associated with CSF fistula as shown by increased immobilization and follow-up surgeries for postoperative CSF fistula which emphasizes the importance to develop strategies to minimize the risk for incidental durotomy.
Gesehen am 28.11.2018